Insufficient repeatability and reproducibility of MALDI-TOF MS-based identification of MRSA - Paskova, Veronika; Chudejova, Katerina; Sramkova, Anna; Kraftova, Lucie; Jakubu, Vladislav; Petinaki, Efthimia A; Zemlickova, Helena; Neradova, Katerina; Papagiannitsis, Costas C; Hrabak, Jaroslav (Folia microbiologica, 2020)
Rapid identification of methicillin-resistant Staphylococcus aureus (MRSA) is essential for proper initial antibiotic therapy and timely set up of hygienic measures. Recently, detection of MRSA using MALDI-TOF mass spectrometer mediated by the peptide-phenol-soluble modulin (PSM-mec)-linked to the class A mec gene complex present in SCCmec cassettes types II, III, and VIII of MRSA strains, has been commercially available. We present here a multicentre study on MALDI-TOF MS detection of MRSA evincing a poor repeatability and reproducibility of the assay. The sensitivity of the assay varies between 50 and 90% in strains carrying psmMEC and psmδ genes encoding for PSM-mec and δ-toxin (a member of the PSM peptide family), respectively. No false positive results were found. The very major error calculation was 30% and the major error achieved 0%. Interlaboratory repeatability varies between 0 and 100%. No significant difference was observed with the use of different cultivation media. Our data showed a poor sensitivity of the method excluding it from the use in routine laboratory testing.
Keywords: Staphylococcal Infections; Sensitivity and Specificity; senzitivita a specificita; Molecular Diagnostic Techniques; Humans; PSM; diagnostické testy rutinní; diagnostické techniky molekulární; stafylokokové infekce; Methicillin-Resistant Staphylococcus aureus; lidé; MALDI-TOF MS; chybná diagnóza; reprodukovatelnost výsledků; MRSA; methicilin rezistentní Staphylococcus aureus; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Reproducibility of Results; Bacterial Toxins; bakteriální toxiny; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Diagnostic Errors; Diagnostic Tests, Routine